Gamma rays induced genetic variability in tomato (Solanum lycopersicum L.) germplasm - Zafar, Syed Ali; Aslam, Muhammad; Albaqami, Mohammed; Ashraf, Awais; Hassan, Arbaz; Iqbal, Junaid; Maqbool, Amir; Naeem, Muhammad; Al-Yahyai, Rashid; Tan, Ali Kee Zuan (Elsevier BV, 2022)
The present study assessed the effectiveness of gamma radiation in inducing favorable genetic variability in tomato (Solanum lycopersicum L.). An experiment was conducted in a randomized complete block design to produce M1 generation. Significant differences were observed among the genotypes as well as between the treatments at individual plant level based on observed traits (seed germination percentage, seedling survival, plant height, number of flower clusters plant−1, number of flowers and fruits plant−1). All observed characters in the mutagenized population were adversely affected with increasing radiation dose. Results identified 450 Gy as the most damaging radiation dose followed by 300 Gy and 150 Gy. Moreover, 300 Gy treatment was identified as lethal dose (LD50) as it caused a 50% germination inhibition in almost all the evaluated genotypes. The 150 Gy treatment showed the least damaging impact and induced maximum genetic variability in almost all the genotypes under study. Character association studies were also conducted which could be utilized in the selection of desirable mutants. Correlation studies revealed an altered association among the observed parameters from positive to negative direction in 300 Gy and 450 Gy treatments as compared to control. These deviations in correlation coefficients proved that mutagenesis can break the linkage among specific loci. Furthermore, path coefficient analysis identified the growth attributes with an effective direct and indirect contribution in yield.